Construction of brick wall / Muhammad Azim Zamaludin - Zamaludin, Muhammad Azim (Universiti Teknologi Mara, Perak, 2016)
DIMARA GROUP was originated in 1995 with the incorporation of Dimara Holdings Sdn Bhd by individuals of diverse background and experience with a view pulling together their financial resources, synergies their respective networking and experience to create a smart partnership to undertake general construction business. Future growth prospects are extremely positive for Dimara Group continuously. The Group are committed to achieve high levels of standards in all projects undertaken and to meet expectation of their shareholders.